Growth hormone receptor gene polymorphism. Spontaneous catch up growth in small for gestational age patients - Perez Garrido, Natalia Isabel (2021)
The growth hormone receptor (GHR) mediates the effect of growth hormone (GH) on linear growth and metabolism. In humans, it exists as two isoforms differing by the retention or exclusion of exon 3; a full-length GHR isoform (GHRfl) and the exon 3-deleted isoform (GHRd3). The genotypic frequency of this polymorphism was analyzed in several studies and in different human populations. However scarce information in Argentinean population is available. Associations between GHRd3 and growth have been reported previously. Some studies have shown that the presence of GHRd3 polymorphism might be a potential variant that improves growth response to recombinant human GH (rhGH) therapy in patients born small for gestational age (SGA), among others. However, over the years the results have been controversial and inconclusive. Based on this, it would be proposed that variants at the genomic level are not completely reflected at the mRNA level. Our aim was to evaluate the genotypic frequencies (%) of the GHR gene polymorphism (GHRfl/GHRfl; GHRfl/GHRd3; GHRd3/GHRd3) in normal Argentinean population (n = 94) and SGA patients (n = 65), and the expression of these polymorphisms at mRNA level in the fetal side of placenta tissues was analyzed. In addition, their association with spontaneous postnatal catch-up growth in SGA patients was also evaluated. In this study, we show a significant increment of compensatory growth in small for gestational age children (SGA) associated to the presence of the GHRd3 allele polymorphism. In addition, the expression of GHR in healthy placentas revealed that no alternative splicing mechanism occurs.